Geometric nonlinear static and dynamic analysis of guyed towers using fully nonlinear element formulations. (15th September 2015) - Shi, H.; Salim, H.
Highlights: Developed FEM elements with full nonlinear element formulations and corresponding algorithms. Nonlinear static and dynamic complex responses of guyed towers. Comparison with available commercial FEM software packages. Developed and evaluated linear assessment method for static response of guyed tower. Examples of guyed tower's nonlinear static and dynamic response. Abstract: The nonlinear responses of guyed towers under static loads and under dynamic loads are investigated by using the developed nonlinear Finite Element Method (FEM). Through the use of the developed fully nonlinear element formulations for structural components such as trusses, cables, and beams, it is possible to capture the complete geometric nonlinear response with the assistance of iterative algorithms such as Crisfield's method and the Newmark beta method. One 50 ft high guyed tower subjected to a constant top-concentrated load and one 328 ft guyed tower subjected to an EI Centro earthquake are used as demonstration. The results of the static analysis are compared with the results from SAP2000, ANSYS, and a linear equivalent column method. The results of the SAP2000, ANSYS, and the developed nonlinear FEM algorithm match well when the deflection is relatively small. In the Linear Equivalent Method, the equivalent spring-supported beam method provides the most accurate estimation when the deflection is relatively small. The complete time history of the guyed tower is also obtained for the nonlinear dynamic analysis.